2020
DOI: 10.1039/c9cp01556f
|View full text |Cite
|
Sign up to set email alerts
|

Structural control of the dielectric, pyroelectric and ferroelectric properties of poly(vinylidene fluoride-co-trifluoroethylene) thin films

Abstract: P(VDF-TrFE) is optimized effectively via thermal treatment and its molecular motions after poling are revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Information about the phase behavior in the vicinity of T c can be obtained from DSC measurements and from the T -dependence of the dielectric function, as depicted in Figures and , respectively. Thermal treatment can affect the crystallinity and the exact temperature of the Curie transition. , Specifically, it was shown that annealing at temperatures above T c results in higher crystallinity of the PE phase. Furthermore, the formation of different ferroelectric crystalline phases with different thermodynamic stability (conformational and packing defects) has been reported following annealing at temperatures below the T c . , Here, the P­(VDF-TrFE) copolymers were annealed at 413 K (a temperature in the region between the Curie and melting transitions) for 2 h. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Information about the phase behavior in the vicinity of T c can be obtained from DSC measurements and from the T -dependence of the dielectric function, as depicted in Figures and , respectively. Thermal treatment can affect the crystallinity and the exact temperature of the Curie transition. , Specifically, it was shown that annealing at temperatures above T c results in higher crystallinity of the PE phase. Furthermore, the formation of different ferroelectric crystalline phases with different thermodynamic stability (conformational and packing defects) has been reported following annealing at temperatures below the T c . , Here, the P­(VDF-TrFE) copolymers were annealed at 413 K (a temperature in the region between the Curie and melting transitions) for 2 h. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…31−33 The transition temperatures between the different crystalline phases are prone to copolymer composition, 22,28 processing (solvent-casting, spin-coating, etc. ), 25,29,34 mechanical drawing or poling, [23][24][25]34 and thermal treatment. 23−25,34−36 For compositions higher than 70 mol %, it was demonstrated (i) a strong thermal hysteresis at T c 37,38 and (ii) an approximately linear increase at T c with pressure, 39,40 suggesting a first-order transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both fluoropolymers, we observed a typical rice grain-like structure, a well-known feature of P(VDF-TrFE)-based formulation for polymerization pro-cesses at temperatures below the paraelectric temperature, T para (ferroelectric-paraelectric phase transition). For the copolymer composition used in this work (monomers ratio of 70:30), a paraelectric temperature of 130 • C has been previously reported [41]. Annealing of the PVDF-based polymer films at different temperatures is expected to induce drastic changes in surface morphology: from rice-grain (<T para ) to a rod-like structure (~T para ), where surrounding non-crystalline molecules are further incorporated, to lamella-structure for higher temperature (>T para ).…”
Section: Dielectric Characterization Of P(vdf)-based Filmsmentioning
confidence: 93%
“…Poly­(vinylidene fluoride) (PVDF), as a stimuli-response biomaterial with significant piezoelectricity, pyroelectricity, triboelectricity, and ferroelectricity properties, has shown several potential medical device applications as wearable sensors, personal health monitoring, and electronic skin among others. The ability to harvest low-level electrical energy in response to energy from the external environment has raised the possibilities to obtain self-powered medical devices. , Wearable medical devices based on energy harvesting from the surroundings can make devices smart, more compact, and IoT-enabled, with very low consumption of power. They can effectively deploy for real-time, personalized, and remote monitoring of several vital parameters of patients, such as oxygen level, glucose concentration, and heart and breath rates.…”
Section: Introductionmentioning
confidence: 99%